ELISA IMMUNO ASSAY IN DISEASE DIAGNOSIS - Daminov Feruz Asadullaevich; Isomadinova Lola Kamoliddinovna; Rashidov Abdurauf (TADQIQOTLAR.UZ, 2024)
Annotation. The article shows the capabilities of a modern serological research method - enzyme immunoassay in the diagnosis of infectious, endocrine and oncological diseases. Practical examples of diagnosing individual pathological conditions, factors influencing the result, and the diagnostic value of the markers used are considered.